2019
DOI: 10.3389/fonc.2019.01412
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenetic, Prognostic, and Therapeutic Role of Fatty Acid Synthase in Human Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common solid tumors worldwide, characterized by clinical aggressiveness, resistance to conventional chemotherapy, and high lethality. Consequently, there is an urgent need to better delineate the molecular pathogenesis of HCC to develop new preventive and therapeutic strategies against this deadly disease. Noticeably, emerging evidence indicates that proteins involved in lipid biosynthesis are important mediators along the development and progression of HCC in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 65 publications
0
39
1
Order By: Relevance
“…Furthermore, TVB2640 is currently under evaluation, alone or in combination with other drugs, in non-small cell lung carcinoma, HER2-positive advanced breast cancer, colorectal cancer, and high-grade relapsed astrocytoma as well as in subjects with non-alcoholic steatohepatitis (NCT03808558, NCT03179904, NCT02980029, NCT03032484, and NCT03938246). In addition, it has been demonstrated in experimental models that FASN inhibitors synergize with multiple chemotherapeutic agents and that FASN blockade restores the sensitivity to chemotherapeutic drugs and targeted therapies [ 49 ]. Based on these encouraging data and in the light of the problems in directly targeting the c-MYC protooncogene, the use of FASN inhibitors might represent a valid therapeutic approach for HCC, at least in the tumor subset showing activation of c-MYC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TVB2640 is currently under evaluation, alone or in combination with other drugs, in non-small cell lung carcinoma, HER2-positive advanced breast cancer, colorectal cancer, and high-grade relapsed astrocytoma as well as in subjects with non-alcoholic steatohepatitis (NCT03808558, NCT03179904, NCT02980029, NCT03032484, and NCT03938246). In addition, it has been demonstrated in experimental models that FASN inhibitors synergize with multiple chemotherapeutic agents and that FASN blockade restores the sensitivity to chemotherapeutic drugs and targeted therapies [ 49 ]. Based on these encouraging data and in the light of the problems in directly targeting the c-MYC protooncogene, the use of FASN inhibitors might represent a valid therapeutic approach for HCC, at least in the tumor subset showing activation of c-MYC.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports in the literature have indicated the relevance of fatty acid synthesis in HCC [42–44]. Immunohistochemical staining showed that the key regulatory enzyme, the fatty acid synthase, was positively expressed in all 20 HCC patients studied, whereas the positive expression rate in tumor‐adjacent tissue was only 10% [43].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is generated by the mevalonate pathway, by condensation of two AcCoA molecules to form 3-HMGCoA, which is then reduced to form mevalonate, and then isoprenoid farnesyl-pyrophosphate. Several studies have shown that targeting the synthesis of cholesterol inhibits cancer cell proliferation and transformation (56).…”
Section: Activation Of De Novo Lipogenesis and Cholesterogenesismentioning
confidence: 99%
“…When the intracellular levels of cholesterol are high, insulin-induced genes interact with SREBP-cleavage-activating proteins (SCAPs) to retain SREBP inactive precursors attached to the ER. When cholesterol levels are low, SCAPs facilitate the translocation SREBPs to the Golgi apparatus to be further processed releasing the active forms (56). SREBP1 promotes the expression of lipogenic genes; meanwhile, SREBP2 regulates the expression of genes involved in the synthesis, uptake, and efflux of cholesterol.…”
Section: Activation Of De Novo Lipogenesis and Cholesterogenesismentioning
confidence: 99%